A PEO-PVDF-based composite halide solid-state electrolyte membrane, a preparation method and application thereof

CN122800729APending Publication Date: 2026-09-22WUHU LIUFANG ION TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610996247.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

但卤化物填料与聚合物基体之间易发生团聚,无法充分发挥其性能优势

Benefits of technology

[0037]1. 本发明提供的PEO-PVDF基复合卤化物固态电解质膜,通过PEO与PVDF的共混设计,充分结合二者优势,PEO保证了电解质与锂金属负极的优异界面兼容性,大幅降低界面阻抗,抑制界面副反应;PVDF提供刚性聚合物骨架,显著提升复合膜的机械强度与耐湿性,二者协同解决了单一基体的性能短板。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122800729A_ABST
    Figure CN122800729A_ABST
Patent Text Reader

Abstract

The application discloses a PEO-PVDF-based composite halide solid electrolyte film and a preparation method and application thereof, and belongs to the technical field of lithium ion battery solid electrolytes, wherein the PEO-PVDF-based composite halide solid electrolyte film is composed of PEO and PVDF as a polymer matrix, modified halide solid electrolyte as active filler, and lithium salt; through the synergistic matrix design of PEO and PVDF, the interface compatibility of the electrolyte and the lithium metal negative electrode is considered, and at the same time, the mechanical properties of the electrolyte film are significantly improved by relying on the rigid skeleton of PVDF and the reinforcing effect of the halide filler; through the uniform dispersion and surface modification of the halide filler, a water vapor blocking path is constructed, and the air stability and moisture resistance of the electrolyte are greatly improved; the electrolyte has high room-temperature ionic conductivity, a wide electrochemical window and stability to the lithium metal negative electrode, the preparation process is simple and controllable, is suitable for large-scale production, and has a wide application prospect in high-energy-density lithium metal solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid electrolyte technology for lithium-ion batteries, specifically relating to a PEO-PVDF-based composite halide solid electrolyte membrane, its preparation method, and its application. Background Technology

[0002] With the rapid development of the new energy industry, traditional liquid lithium-ion batteries can no longer meet the demands of high-energy-density energy storage devices. Lithium metal solid-state batteries, due to their high theoretical energy density and good safety, have become the core development direction of next-generation energy storage technology. Solid electrolytes, as the core component of lithium metal solid-state batteries, directly determine the battery's electrochemical performance, cycle life, and safety performance.

[0003] Polymer solid electrolytes are among the most promising solid electrolyte systems for industrialization due to their good flexibility, excellent interfacial contact, and ease of processing and molding. Among them, polyethylene oxide (PEO) is the most widely studied polymer matrix. It has excellent solubility for lithium salts and good interfacial compatibility with lithium metal anodes. However, pure PEO has defects such as low room temperature ionic conductivity, poor mechanical strength, easy crystallization, poor air stability, and extreme hygroscopicity and hydrolysis. It cannot effectively inhibit lithium dendrite growth, and it is difficult to process and store in air.

[0004] Polyvinylidene fluoride (PVDF) has excellent mechanical strength, electrochemical stability, moisture resistance and oxidation resistance. Its strong polar CF bond can promote the dissociation of lithium salts. However, it has poor interfacial compatibility with lithium metal anodes, high interfacial impedance, and is prone to interfacial side reactions during cycling, making it difficult to use as an electrolyte matrix for lithium metal batteries alone.

[0005] Using PEO and PVDF blends as a polymer matrix can improve the dimensional stability and heat resistance of the composite electrolyte by introducing rigid PVDF components, but the system still suffers from insufficient room temperature ionic conductivity.

[0006] Chinese patent CN 116632336 A discloses a solid electrolyte film, its preparation method, and a lithium battery. The solid electrolyte film includes a polymer material, a lithium salt, and an inorganic active filler. The polymer material includes a styrene-diacrylate-styrene block polymer, and the inorganic active filler includes one or more of γ-LiAlO2, Li3N, LATP, and LLZTO. These inorganic active fillers generally have low ionic conductivity, high interfacial impedance, high rigidity, and poor processability, making it difficult to form an effective composite with the polymer matrix. Furthermore, oxide fillers tend to form a passivation layer at the interface, hindering lithium-ion conduction and exacerbating interfacial polarization.

[0007] Halide solid electrolytes offer advantages such as high room temperature ionic conductivity, a wide electrochemical window, and compatibility with high-voltage cathodes. Furthermore, compared to sulfide solid electrolytes, they exhibit better chemical stability to lithium metal and lower sensitivity to air and moisture, making them ideal active fillers for composite polymer electrolytes. However, halide fillers are prone to agglomeration with the polymer matrix, hindering the full realization of their performance advantages. Summary of the Invention

[0008] To address the aforementioned technical problems, this invention provides a PEO-PVDF-based composite halide solid electrolyte membrane and its preparation method. Through the synergistic effect of the PEO-PVDF dual matrix and the modification and optimization of the halide active filler, it achieves stable compatibility with lithium metal anodes while significantly improving the mechanical strength, air stability, and moisture resistance of the electrolyte.

[0009] This invention also provides a method for preparing the PEO-PVDF-based composite halide solid electrolyte membrane. The method uses a solution casting method, which has simple and controllable process steps, requires no complex equipment, has relaxed production environment requirements, is compatible with existing lithium-ion battery production processes, and has good prospects for industrial application.

[0010] This invention also provides the application of the PEO-PVDF-based composite halide solid electrolyte membrane in lithium-ion batteries. Lithium-ion batteries prepared using this membrane as the electrolyte layer exhibit excellent interfacial stability between the electrolyte layer and the lithium metal anode. The lithium-ion battery operates at 0.1 mA cm⁻¹. -2 It can cycle stably for more than 1000 hours at a current density without short circuit or significant voltage polarization; it is compatible with cathodes such as lithium iron phosphate and high-voltage ternary lithium, and the assembled full cells have excellent cycle performance and rate performance.

[0011] The technical solution adopted in this invention is as follows:

[0012] This invention provides a PEO-PVDF-based composite halide solid electrolyte membrane, wherein the raw materials of the composite halide solid electrolyte membrane include a PEO and PVDF blend matrix, a modified halide solid electrolyte, a lithium salt, and optional plasticizers and film-forming aids.

[0013] The amounts of modified halide solid electrolyte, lithium salt, plasticizer, and film-forming aid are 5-80 wt%, 10-50 wt%, 0-20 wt%, and 0-5 wt%, respectively, of the amount of PEO and PVDF blend matrix.

[0014] Furthermore, the amounts of the modified halide solid electrolyte, lithium salt, plasticizer, and film-forming aid are preferably 20-60 wt%, 20-40 wt%, 0-10 wt%, and 0-3 wt%, respectively, of the PEO and PVDF blend matrix.

[0015] In the PEO and PVDF blend matrix, the mass ratio of PEO to PVDF is (3~7):(7~3).

[0016] The modified halide solid electrolyte is obtained by coating and modifying the halide solid electrolyte with a modifier; the modifier is a polyether-type silane or a fluorosilane coupling agent; the amount of the modifier is 0.5~5% of the mass of the halide solid electrolyte powder.

[0017] The preparation method of the modified halide solid electrolyte includes the following steps:

[0018] 1) The halide solid electrolyte was ball-milled in an argon inert atmosphere to obtain ultrafine powder with a D50 particle size of 0.1~5 μm;

[0019] 2) Disperse the ball-milled powder in anhydrous DME to prepare a dispersion with a solid content of 5%~10%. Add polyether-type silane or fluorosilane coupling agent and stir the mixture at 40~60 ℃ for 6~24 h in an argon atmosphere. After the reaction is completed, centrifuge the mixture, wash it three times with anhydrous DME, and vacuum dry it at 60~80 ℃ for 12~24 h. The water and oxygen content is controlled to be <0.1 ppm throughout the process to obtain the modified halide solid electrolyte.

[0020] In step 1), the ball milling parameters are: ball-to-material ratio (10~20):1, rotation speed 300~500 rpm, and ball milling time 2~4 h.

[0021] The general formula of the halide solid electrolyte is Li α M β X6, wherein M is selected from one or more of the +3 valence metals Y, In, Sc, La, and Ce, and / or one or more of the +4 valence metals Zr and Hf; when M is +3 valence, α=3 and β=1, and when M is +4 valence, α=2 and β=1; X is selected from one or more of Cl, Br, and I; the powder particle size of the halide solid electrolyte is 0.1~5 μm.

[0022] The halide solid electrolyte is preferably one or more of Li3YCl6, Li3InCl6, Li2ZrCl6, Li3YBr6, and Li3InBr6.

[0023] The polyether-type silane is preferably diethylene glycol ether propyltrimethoxysilane or triethylene glycol propyltriethoxysilane.

[0024] The lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorooxalateborate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), and lithium perchlorate (LiClO4), with LiTFSI being preferred.

[0025] The plasticizer is selected from one or more of triethyl phosphate (TEP), trimethyl phosphate (TMP), adiponitrile (ADN), succinic anhydride (SN), and glutaronitrile (GN).

[0026] The film-forming aid is selected from one or more of polyethylene glycol dimethyl ether (PEGDME), triethylene glycol dimethyl ether (G3), and sulfolane (SL).

[0027] The present invention also provides a method for preparing the PEO-PVDF-based composite halide solid electrolyte membrane, the method comprising the following steps:

[0028] (1) Dissolve the PEO and PVDF blend matrix in an organic solvent, add lithium salt, modified halide solid electrolyte and optional plasticizer and film-forming aid to it, stir and mix evenly in an inert atmosphere to obtain casting solution;

[0029] (2) The casting liquid is cast into a film and dried to obtain the PEO-PVDF-based composite halide solid electrolyte membrane.

[0030] In step (1), the organic solvent is one or more of ethylene glycol dimethyl ether (DME), dichloromethane (DCM), 1,3-dioxolane (DOL), and acetone.

[0031] In step (2), the thickness of the cast film is 100~300 μm.

[0032] In step (2), the drying is carried out in a stepwise manner. First, the solvent is allowed to evaporate initially in an inert atmosphere at room temperature for 2-6 hours. Then, it is transferred to a vacuum drying oven at 60-80°C for 4 hours for pre-drying. Finally, the temperature is raised to 100-120°C for vacuum drying for 12-24 hours.

[0033] The present invention also provides the application of the PEO-PVDF-based composite halide solid electrolyte membrane in solid-state lithium-ion batteries.

[0034] The present invention also provides a solid-state lithium-ion battery, wherein the solid-state lithium-ion battery uses the PEO-PVDF-based composite halide solid electrolyte membrane described in the present invention as the electrolyte layer.

[0035] The negative electrode of the solid-state lithium-ion battery is a lithium metal sheet, a lithium alloy sheet, or a composite lithium negative electrode; the positive electrode is one or more of lithium iron phosphate, ternary layered oxide, lithium-rich manganese-based oxide, and high-pressure lithium cobalt oxide.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1. The PEO-PVDF-based composite halide solid electrolyte membrane provided by the present invention fully combines the advantages of PEO and PVDF through a blending design. PEO ensures excellent interfacial compatibility between the electrolyte and the lithium metal anode, significantly reduces interfacial impedance, and suppresses interfacial side reactions. PVDF provides a rigid polymer skeleton, which significantly improves the mechanical strength and moisture resistance of the composite membrane. The two work together to solve the performance shortcomings of a single matrix.

[0038] 2. The PEO-PVDF-based composite halide solid electrolyte membrane provided by this invention uses a surface-modified halide solid electrolyte as the active filler. Compared with commonly used fillers in the prior art such as γ-LiAlO2, Li3N, LATP, and LLZTO, it has the following superior comprehensive performance:

[0039] 1) Improved ionic conductivity: Halogen solid electrolytes themselves have high ionic conductivity, which effectively improves the interfacial compatibility between halide solid electrolytes and polymer matrices, avoids powder agglomeration, inhibits PEO crystallization, constructs a polymer-filler dual continuous lithium-ion conduction channel, and improves room temperature ionic conductivity, which is much higher than that of systems using conventional oxide fillers.

[0040] 2) Significantly improved moisture resistance: The halide solid electrolyte uniformly dispersed in the PEO polymer matrix has a dense water vapor barrier structure. Combined with surface hydrophobic modification, after being placed in air with a relative humidity of 10% for 24 hours, the PEO-PVDF-based composite halide solid electrolyte membrane provided by this invention has a high ionic conductivity retention rate, which solves the pain point of traditional PEO-based electrolytes being easy to absorb moisture and unable to be processed and stored in air.

[0041] 3) Synergistic enhancement of mechanical properties: Using modified halide solid electrolyte as active filler, it has good interfacial bonding with polymer matrix. The PEO-PVDF based composite halide solid electrolyte membrane provided by this invention has high tensile strength, which can effectively inhibit lithium dendrite growth and ensure the long-cycle stability of battery.

[0042] 3. In the PEO-PVDF-based composite halide solid electrolyte membrane provided by this invention, the strong polar CF bonds of PVDF interact with the functional groups on the surface of the modified halide solid electrolyte, enhancing the interfacial bonding force. Simultaneously, the flexible segments of PEO can alleviate the interfacial stress between the modified halide solid electrolyte and the matrix, preventing the electrolyte membrane from cracking during cycling. This synergistic effect enables the PEO-PVDF-based composite halide solid electrolyte membrane provided by this invention to simultaneously possess high ionic conductivity, high mechanical strength, and excellent interfacial stability, which is unattainable with a single matrix or conventional filler system.

[0043] 4. The PEO-PVDF-based composite halide solid electrolyte membrane provided by this invention has an ionic conductivity ≥1×10⁻⁶ at room temperature. -4 S cm -1 Electrochemical oxidation window ≥ 4.8V (vs Li / Li + It exhibits excellent interfacial stability with lithium metal anodes, enabling lithium symmetric cells to operate at 0.1 mA cm⁻¹. -2 It can cycle stably for more than 1000 hours at a current density without short circuit or significant voltage polarization; it is compatible with cathodes such as lithium iron phosphate and high-voltage ternary lithium, and the assembled full cells have excellent cycle performance and rate performance.

[0044] 5. Simple preparation process, suitable for large-scale production: This invention uses the conventional solution casting method for preparation. The process steps are simple and controllable, no complex equipment is required, the production environment requirements are relaxed, it is compatible with existing lithium-ion battery production processes, and has good prospects for industrial application. Attached Figure Description

[0045] Figure 1 This is a schematic diagram of the structure of the PEO-PVDF-based composite halide solid electrolyte membrane provided by the present invention. Detailed Implementation

[0046] The present invention will now be described in detail with reference to the embodiments.

[0047] In the following examples and comparative examples, all raw materials used were battery grade. The molecular weight of PEO was 1 million to 6 million, PVDF was battery grade polyvinylidene fluoride, and lithium salt and halide solid electrolyte were anhydrous battery grade. Except for the air stability test, the entire process was carried out in an argon glove box with a water oxygen content of <0.1ppm.

[0048] Example 1

[0049] A PEO-PVDF-based composite halide solid electrolyte membrane is disclosed, comprising a PEO and PVDF blend matrix, diethylene glycol ether propyltrimethoxysilane-modified Li3YCl6 powder, and LiTFSI. Based on the total mass of the PEO and PVDF blend matrix, 30 wt% LiTFSI and 40 wt% diethylene glycol ether propyltrimethoxysilane-modified Li3YCl6 powder are incorporated; the mass ratio of PEO to PVDF in the PEO and PVDF blend matrix is ​​50:50. The composite halide solid electrolyte membrane is prepared by preparing a casting solution from the above raw materials.

[0050] The preparation method of the PEO-PVDF-based composite halide solid electrolyte membrane is as follows:

[0051] (1) LYC powder modification: Li3YCl6 powder was ball-milled for 3 h in an argon atmosphere in a glove box with a ball-to-powder ratio of 15:1 and a rotation speed of 400 rpm to obtain ultrafine LYC powder with D50=1 μm; the powder was dispersed in anhydrous DME to prepare a dispersion with a solid content of 8wt%, and 2% of the powder mass of diethylene glycol ether propyltrimethoxysilane was added. The mixture was stirred at 50 ℃ for 12 h, centrifuged, washed 3 times with anhydrous DME, and vacuum dried at 80 ℃ for 24 h to obtain LYC powder modified with diethylene glycol ether propyltrimethoxysilane.

[0052] (2) Preparation of casting solution: In an argon glove box, PEO and PVDF with a mass ratio of 50:50 were used as the blend matrix and dispersed in anhydrous DME. The solid-liquid ratio was controlled at 1:8 and stirred at 60 °C until completely dissolved to obtain a transparent polymer solution. LiTFSI equivalent to 30% of the total mass of the blend matrix was added and stirred until completely dissolved. Then, diethylene glycol ether propyltrimethoxysilane modified LYC powder equivalent to 40 wt% of the total mass of the blend matrix was added and stirred continuously for 24 h to obtain a uniform casting solution without agglomeration.

[0053] (3) Film drying: The casting solution was coated on a glass plate with a scraper, the wet film thickness was 200 μm, and it was left to stand at room temperature in a glove box for 4 h. Then it was transferred to a vacuum drying oven, pre-dried at 80 ℃ for 4 h, and vacuum dried at 110 ℃ for 20 h to completely remove the solvent. After cooling, it was demolded to obtain a self-supporting PEO-PVDF-based composite halide solid electrolyte membrane with a thickness of 120 μm.

[0054] Example 2

[0055] A PEO-PVDF-based composite halide solid electrolyte membrane is disclosed, comprising a PEO and PVDF blend matrix, diethylene glycol ether propyltrimethoxysilane-modified Li3InCl6 powder, LiTFSI, and succinate, wherein succinate is used as a plasticizer. Based on the total mass of the PEO and PVDF blend matrix, 25 wt% LiTFSI, 30 wt% diethylene glycol ether propyltrimethoxysilane-modified Li3InCl6 powder, and 10 wt% succinate are added. The mass ratio of PEO to PVDF in the PEO and PVDF blend matrix is ​​70:30. The above raw materials are formulated into a casting solution to prepare the PEO-PVDF-based composite halide solid electrolyte membrane.

[0056] The preparation method of the PEO-PVDF-based composite halide solid electrolyte membrane is as follows:

[0057] (1) Modification of Li3InCl6 powder: Li3InCl6 powder was ball-milled in an argon atmosphere in a glove box for 2 h with a ball-to-powder ratio of 20:1 and a rotation speed of 500 rpm to obtain ultrafine Li3InCl6 powder with D50=1 μm; the powder was dispersed in anhydrous DME to prepare a dispersion with 8wt% solid content, and 2% of the powder mass of diethylene glycol ether propyltrimethoxysilane was added. The mixture was stirred at 50 ℃ for 12 h, centrifuged, washed 3 times with anhydrous DME, and vacuum dried at 80 ℃ for 24 h to obtain Li3InCl6 powder modified with diethylene glycol ether propyltrimethoxysilane.

[0058] (2) Preparation of casting solution: In an argon glove box, PEO and PVDF with a mass ratio of 70:30 were used as the blend matrix and dispersed in anhydrous DME. The solid-liquid ratio was controlled at 1:7 and stirred at 60 °C until completely dissolved to obtain a transparent polymer solution. LiTFSI equivalent to 25% of the total mass of the blend matrix was added and stirred until completely dissolved. Then, diethylene glycol ether propyltrimethoxysilane modified Li3InCl6 powder equivalent to 30 wt% of the total mass of the blend matrix and succinic anionizer equivalent to 10% of the total mass of the blend matrix were added and stirred continuously for 24 h to obtain a uniform casting solution without agglomeration.

[0059] (3) Film drying: The casting solution was coated on a glass plate with a scraper, the wet film thickness was 200 μm, and it was left to stand at room temperature in a glove box for 4 h. Then it was transferred to a vacuum drying oven, pre-dried at 80 ℃ for 4 h, and vacuum dried at 110 ℃ for 20 h to completely remove the solvent. After cooling, it was demolded to obtain a self-supporting PEO-PVDF-based composite halide solid electrolyte membrane with a thickness of 120 μm.

[0060] Example 3

[0061] A PEO-PVDF-based composite halide solid electrolyte membrane is disclosed, comprising a PEO and PVDF blend matrix, diethylene glycol ether propyltrimethoxysilane-modified Li₂ZrCl₆ powder, and LiTFSI. Based on the total mass of the PEO and PVDF blend matrix, 35 wt% of LiTFSI and 50 wt% of diethylene glycol ether propyltrimethoxysilane-modified Li₂ZrCl₆ powder are added; the mass ratio of PEO to PVDF in the PEO and PVDF blend matrix is ​​30:70. The above raw materials are formulated into a casting solution to prepare the PEO-PVDF-based composite halide solid electrolyte membrane.

[0062] The preparation method of the PEO-PVDF-based composite halide solid electrolyte membrane is as follows:

[0063] (1) Modification of Li2ZrCl6 powder: Li2ZrCl6 powder was ball-milled for 3 h in an argon atmosphere in a glove box with a ball-to-powder ratio of 15:1 and a rotation speed of 400 rpm to obtain ultrafine Li2ZrCl6 powder with D50=1 μm; the powder was dispersed in anhydrous DME to prepare a dispersion with a solid content of 8wt%, and 2% of the powder mass of diethylene glycol ether propyltrimethoxysilane was added. The mixture was stirred at 50 ℃ for 12 h, centrifuged, washed 3 times with anhydrous DME, and vacuum dried at 80 ℃ for 24 h to obtain Li2ZrCl6 powder modified with diethylene glycol ether propyltrimethoxysilane.

[0064] (2) Preparation of casting solution: In an argon glove box, PEO and PVDF with a mass ratio of 30:70 were used as the blend matrix and dispersed in anhydrous DME. The solid-liquid ratio was controlled at 1:9 and stirred at 60 °C until completely dissolved to obtain a transparent polymer solution. LiTFSI equivalent to 35% of the total mass of the blend matrix was added and stirred until completely dissolved. Then, diethylene glycol ether propyltrimethoxysilane modified Li2ZrCl6 powder equivalent to 50wt% of the total mass of the blend matrix was added and stirred continuously for 24 h to obtain a uniform casting solution without agglomeration.

[0065] (3) Film drying: The casting solution was coated on a glass plate with a scraper, the wet film thickness was 200 μm, and it was left to stand at room temperature in a glove box for 4 h. Then it was transferred to a vacuum drying oven, pre-dried at 80 ℃ for 4 h, and vacuum dried at 110 ℃ for 20 h to completely remove the solvent. After cooling, it was demolded to obtain a self-supporting PEO-PVDF-based composite halide solid electrolyte membrane with a thickness of 120 μm.

[0066] Comparative Example 1

[0067] A PEO-PVDF-based composite halide solid electrolyte membrane differs from Example 1 only in that the diethylene glycol ether propyltrimethoxysilane modified Li3YCl6 powder is replaced with an equal mass of Li3YCl6 powder.

[0068] The preparation method of the PEO-PVDF-based composite halide solid electrolyte membrane is the same as in Example 1.

[0069] Comparative Example 2

[0070] A PEO-PVDF-based composite oxide solid electrolyte membrane differs from Example 1 only in that the diethylene glycol ether propyltrimethoxysilane modified Li3YCl6 powder is replaced with an equal mass of diethylene glycol ether propyltrimethoxysilane modified LLZTO powder, and the modification method is the same as in Example 1.

[0071] The preparation method of the PEO-PVDF-based composite oxide solid electrolyte membrane is the same as in Example 1.

[0072] Comparative Example 3

[0073] A PVDF-based composite halide solid electrolyte membrane differs from Example 1 only in that all PEO is replaced with an equal mass of PVDF, while the rest of the formulation, preparation steps and parameters are the same as in Example 1.

[0074] Comparative Example 4

[0075] A PEO-PVDF-based solid electrolyte membrane differs from Example 1 only in that: no halide solid electrolyte filler is added, i.e., the addition of diethylene glycol ether propyltrimethoxysilane modified Li3YCl6 powder is omitted; the rest of the formulation, preparation steps and parameters are the same as in Example 1.

[0076] Test case

[0077] The electrolyte membranes prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests, and the test methods are as follows:

[0078] 1. Room temperature ionic conductivity: Using a stainless steel / electrolyte / stainless steel blocking battery structure, the ionic conductivity was measured by electrochemical impedance spectroscopy (EIS) at a frequency of 1 MHz to 0.01 Hz, an AC amplitude of 10 mV, and a test temperature of 25 ℃. The results are shown in Table 1.

[0079] 2. Mechanical properties: The tensile strength of the electrolyte membrane was tested using a universal tensile testing machine at a tensile rate of 5 mm / min and a sample size of 10 mm × 50 mm. The results are shown in Table 1.

[0080] 3. Electrochemical window: A lithium / electrolyte / stainless steel battery structure was used, and the results were measured using linear sweep voltammetry (LSV) at a scan rate of 1 mV / s. -1 Test voltage range 0~5.5 V (vs Li / Li) + The results are shown in Table 1.

[0081] 4. Air stability and moisture resistance: The electrolyte membrane was placed in an air environment of 25 ℃ and 10% relative humidity for 24 h. The ionic conductivity before and after placement was tested, the conductivity retention rate was calculated, and the appearance change of the membrane was observed. The results are shown in Table 1.

[0082] 5. All-Solid-State Battery Performance Testing: The electrolyte membranes prepared in each embodiment and comparative example were cut into 12mm × 12mm pieces to serve as electrolyte membranes for all-solid-state batteries. 30mg of composite cathode powder was uniformly spread on one surface of each membrane and pressed for 3 min. A 30μm thick lithium-indium alloy sheet was then spread on the other surface, and the membranes were assembled into all-solid-state batteries for testing. The composite cathode powder was prepared by mixing NCM9055 and solid electrolyte powder at a mass ratio of 7:3 and grinding for 30 min. The raw material composition of each solid electrolyte powder is the same as that of the electrolyte membrane in each embodiment and comparative example. For example, when using the PEO-PVDF-based composite halide solid electrolyte membrane prepared in Example 1 as the electrolyte membrane to assemble a solid battery, the raw material composition of the solid electrolyte powder used in the composite cathode powder is: PEO and PVDF blend matrix, diethylene glycol ether propyltrimethoxysilane modified Li3YCl6 powder and LiTFSI, wherein the mass of diethylene glycol ether propyltrimethoxysilane modified Li3YCl6 powder and LiTFSI are 40wt% and 30wt% of the mass of PEO and PVDF blend matrix, respectively.

[0083] The test voltage was 2.2~3.68 V. The first two cycles were performed with a current density of 0.05 C (1 C = 200 mAh / g) using a Blue Electric charge-discharge tester. Subsequently, the cycle was performed with a current density of 0.1 C. The test results are summarized in Table 2.

[0084] Table 1

[0085]

[0086] Table 2

[0087]

[0088] The test results in Table 1 show that:

[0089] 1. The PEO-PVDF-based composite halide solid electrolyte membranes prepared in Examples 1-3 of this invention simultaneously achieve high room temperature ionic conductivity, high tensile strength, wide electrochemical window, excellent lithium interface stability and moisture resistance, which are comprehensively superior to the comparative examples.

[0090] 2. In Comparative Example 1, compared to Example 1, the performance of the electrolyte membrane obtained by replacing the diethylene glycol ether propyltrimethoxysilane modified Li3YCl6 powder with an equal mass of Li3YCl6 powder decreased compared to Example 1, demonstrating that surface modification can further improve the interfacial compatibility of the filler and the overall performance of the electrolyte.

[0091] 3. In Comparative Example 2, compared to Example 1, the diethylene glycol ether propyltrimethoxysilane modified Li3YCl6 powder was replaced with an equal mass of diethylene glycol ether propyltrimethoxysilane modified LLZTO powder. The resulting electrolyte membrane had extremely low mechanical strength, could not suppress lithium dendrites, had extremely poor air humidity resistance, and its conductivity decreased significantly after being placed.

[0092] 4. In Comparative Example 3, compared to Example 1, all PEO was replaced with an equal mass of PVDF. The resulting electrolyte membrane had extremely low ionic conductivity, poor compatibility with the lithium metal interface, and severe cyclic polarization.

[0093] 5. In Comparative Example 4, the addition of diethylene glycol ether propyltrimethoxysilane modified Li3YCl6 powder was omitted compared to Example 1. The ionic conductivity, moisture resistance, and mechanical properties of the resulting electrolyte membrane were significantly reduced, demonstrating that the synergistic effect of the PEO-PVDF dual matrix and the modified halide solid electrolyte filler is indispensable.

[0094] The test results in Table 2 show that:

[0095] 1. The all-solid-state batteries assembled from the PEO-PVDF-based composite halide solid electrolyte membranes prepared in Examples 1-3 of this invention all exhibited initial coulombic efficiencies exceeding 80%, and maintained a discharge specific capacity of 188 mAh g⁻¹ after 100 cycles. -1 The capacity retention rate can reach over 80%, and it has excellent first charge / discharge efficiency and long-cycle stability. Its overall electrochemical performance is superior to that of the comparative ratios.

[0096] 2. Compared with Example 1, the battery prepared using unmodified halide filler in Comparative Example 1 showed a significant decline in both initial coulombic efficiency and cycle capacity retention. This indicates that surface coating modification of halide filler can effectively improve the interfacial compatibility between filler and polymer matrix and positive electrode active material, reduce interfacial contact impedance, reduce interfacial side reactions during cycling, and thus improve the charge and discharge efficiency and capacity retention of the battery.

[0097] 3. In Comparative Example 2, the battery using modified LLZTO oxide filler showed a significant deterioration in initial efficiency and cycle performance, further verifying the problems of poor interfacial matching between conventional oxide fillers and polymer matrix and high ion conduction resistance, highlighting the performance advantages of halide solid electrolytes as active fillers in composite polymer systems.

[0098] 4. In Comparative Example 3, the battery using a single PVDF matrix had an initial coulombic efficiency of only 63.9% and significant capacity decay during cycling. This demonstrates the key role of the PEO component in optimizing the compatibility of the electrolyte and electrode interface and reducing interfacial polarization, thus confirming the necessity of the PEO-PVDF dual-matrix synergistic design.

[0099] 5. The battery in Comparative Example 4 without added halide solid electrolyte filler showed the worst performance in all aspects, which fully demonstrates that the synergistic effect of modified halide filler and PEO-PVDF dual matrix is ​​the core guarantee for achieving high specific capacity and long cycle life of all solid-state batteries.

[0100] The above detailed description of a PEO-PVDF-based composite halide solid electrolyte membrane, its preparation method, and its application, with reference to the embodiments, is illustrative rather than limiting. Several embodiments may be listed within the defined scope. Therefore, variations and modifications that do not depart from the overall concept of the present invention should be within the protection scope of the present invention.

Claims

1. A PEO-PVDF-based composite halide solid electrolyte membrane, characterized in that, The raw materials for the composite halide solid electrolyte membrane include a PEO and PVDF blend matrix, a modified halide solid electrolyte, a lithium salt, and optional plasticizers and film-forming aids. The amounts of modified halide solid electrolyte, lithium salt, plasticizer, and film-forming aid are 5-80 wt%, 10-50 wt%, 0-20 wt%, and 0-5 wt%, respectively, of the amount of PEO and PVDF blend matrix.

2. The PEO-PVDF-based composite halide solid electrolyte membrane according to claim 1, characterized in that, The amounts of modified halide solid electrolyte, lithium salt, plasticizer, and film-forming aid are 20-60 wt%, 20-40 wt%, 0-10 wt%, and 0-3 wt%, respectively, based on the amount of PEO and PVDF blend matrix.

3. The PEO-PVDF-based composite halide solid electrolyte membrane according to claim 1 or 2, characterized in that, In the PEO and PVDF blend matrix, the mass ratio of PEO to PVDF is (3~7):(7~3).

4. The PEO-PVDF-based composite halide solid electrolyte membrane according to claim 1 or 2, characterized in that, The modified halide solid electrolyte is obtained by coating and modifying the halide solid electrolyte with a modifier; the modifier is a polyether-type silane or a fluorosilane coupling agent; the amount of the modifier is 0.5~5% of the mass of the halide solid electrolyte powder.

5. The PEO-PVDF-based composite halide solid electrolyte membrane according to claim 4, characterized in that, The general formula of the halide solid electrolyte is Li α M β X6, wherein M is selected from one or more of the +3 valence metals Y, In, Sc, La, and Ce, and / or one or more of the +4 valence metals Zr and Hf; when M is +3 valence, α=3 and β=1, and when M is +4 valence, α=2 and β=1; X is selected from one or more of Cl, Br, and I; the powder particle size of the halide solid electrolyte is 0.1~5 μm.

6. The PEO-PVDF-based composite halide solid electrolyte membrane according to claim 1 or 2, characterized in that, The lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalateborate, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, and lithium perchlorate.

7. The method for preparing the PEO-PVDF-based composite halide solid electrolyte membrane according to any one of claims 1-6, characterized in that, The preparation method includes the following steps: (1) Dissolve the PEO and PVDF blend matrix in an organic solvent, add lithium salt, modified halide solid electrolyte and optional plasticizer and film-forming aid to it, stir and mix evenly in an inert atmosphere to obtain casting solution; (2) The casting liquid is cast into a film and dried to obtain the PEO-PVDF-based composite halide solid electrolyte membrane.

8. The preparation method according to claim 7, characterized in that, In step (1), the organic solvent is one or more of ethylene glycol dimethyl ether, dichloromethane, 1,3-dioxolane, and acetone.

9. The application of the PEO-PVDF-based composite halide solid electrolyte membrane according to any one of claims 1-6 in lithium-ion batteries.

10. A lithium-ion battery, characterized in that, The lithium-ion battery uses the PEO-PVDF-based composite halide solid electrolyte membrane as described in any one of claims 1-6 as the electrolyte layer.

Citation Information

Patent Citations

  • Solid electrolyte film, preparation method thereof and lithium battery

    CN116632336A